Factors influencing Saudi Arabian women's shopping behavior in online purchase activities / Areeg ALMowalad and Lennora Putit - ALMowalad, Areeg; Putit, Lennora (2013)
The paper presented a study on factors influencing shopping behavior amongst women consumers in the Kingdom of Saudi Arabia towards online purchase. This study is conducted to gain a comprehensive knowledge and understanding on the possible factors behind virtual business transaction. It involves 34 Saudi Arabian women representing diverse background ranging from 18 to 35 years old. The interview survey consists of open-ended questions and analyzed through theme analysis procedure. The study yields interesting findings with both trust (45%) and risk (40%) found to be the key indicating factors that affect consumers’ consumption decision making. Finally, several implications and recommendations for future research related to online purchase are subsequently discussed.